INCREASING CONFIDENCE IN THE BANKING SYSTEM OF UKRAINE (World of finance, 2020)
Introduction. Maintaining confidence in the banking system of Ukraine is a key factor in ensuring the successful operation of banks. Furthermore, confidence is the basis on which the activities of financial intermediaries are based.The purpose of the article is to conduct analysis of the level of confidence in the banking system using a number of indicators and to provide recommendations for increasing its level.Results. The concept of trust is more psychological than purely economic has been justified. With number of indicators it is possible to estimate its level has been determined, namely: growth rate and maturity structure of the deposit portfolio, dollarization of deposits, volume and share of cash in money supply. Various rating agencies, which also determine the level of public trust in financial institutions, are considered. According to the results of the analysis during 2008-2020 it is concluded that the level of public confidence in banks is increasing, albeit at a slow pace, which is confirmed by the annual growth rate of the deposit portfolio since 2017. In order to ensure confidence in banks, a comprehensive approach should be applied, involving measures taken by banks, the NBU and the state. Stable macroeconomic situation, sustained economic growth, financial stability of the banking system, lower inflation, and improving the well-being of citizens are the key factors for improving confidence in the banking system.